2023
DOI: 10.3390/nano13020282
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Visible-Light-Responsive Photocatalytic Degradation of Ciprofloxacin by the CuxO/Metal-Organic Framework Hybrid Nanocomposite

Abstract: Ciprofloxacin (CIP) is a commonly used antibiotic, however, once in the environment, it is highly toxic with a poor biodegradability. Given these attributes, an effective strategy for the removal of CIP is urgently needed for the protection of water resources. Herein, a novel copper metal-organic framework (CuxO/MOF) multifunctional material has been produced, in this work, by the calcination of Cu-MOF urea at 300 °C, in the presence of a 5% H2 atmosphere. The morphological, structural, and thermal properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Tsai et al successfully designed a bifunctional Cu x O/MOF in the presence of urea for the photocatalytic degradation of CIP under visible light in an aqueous medium. 43 This could serve as a potential and reliable candidate for establishing a new pathway for the advancement of visible-light-responsive photocatalysts to eliminate antibiotics and other emerging contaminants.…”
Section: Cu-btc Mof-based Photocatalysts For the Photocatalytic Elimi...mentioning
confidence: 99%
“…Tsai et al successfully designed a bifunctional Cu x O/MOF in the presence of urea for the photocatalytic degradation of CIP under visible light in an aqueous medium. 43 This could serve as a potential and reliable candidate for establishing a new pathway for the advancement of visible-light-responsive photocatalysts to eliminate antibiotics and other emerging contaminants.…”
Section: Cu-btc Mof-based Photocatalysts For the Photocatalytic Elimi...mentioning
confidence: 99%
“…The two characteristic peaks at 952.5 and 932.8 eV correspond to the binding energies of Cu + 2p 1/2 and 2p 3/2 electrons, while the two characteristic peaks at 953.8 and 933.8 eV correspond to the binding energies of Cu 2+ 2p 1/2 and 2p 3/2 , respectively. 46,47 In addition, satellite peaks with 2p 1/2 and 2p 3/2 peaks were also observed, corresponding to the electronic oscillation, 48 indicating the presence of Cu 2+ and the coexistence of Cu 2 O and CuO on Cu x O-T. It can be found that in Cu x O-T, the ratio of Cu + /Cu 2+ gradually decreases with the increase in temperature, and the ratio of Cu x O-300 is the highest at other temperatures, while Cu x O-500 is the lowest.…”
Section: Characterization Of the Prepared Samplesmentioning
confidence: 99%